Between continuity and change: CSR managers' occupational rhetorics. Issue 4 (3rd July 2017) - Carollo, Luca; Guerci, Marco
Abstract : Purpose: Corporate social responsibility (CSR) is often depicted as a major challenge to current business practices, and CSR managers have recently been indicated as prime examples of change agents. The purpose of this paper is to take an occupational perspective to consider these managers. It focuses in particular on their occupational rhetorics, which correspond to idealized images that CSR managers use to represent their work. These rhetorics are analyzed in order to shed light on CSR managers' change potential in organizations. Design/methodology/approach: The study, which benefits from collaboration with the Italian CSR Manager Network, draws on a multi-method research approach which included interviews, observations at public events and meetings, as well as focus groups with CSR managers. Findings: Five broad rhetorical repertoires were identified: "the motor of change, " "the business-oriented, " "the fatalist, " "the idealist" and "the CSR bookkeeper" rhetorics. The primacy of the first two repertoires lead to the conclusion that CSR managers are more likely to foster continuity instead of change in current business practices. Research limitations/implications: The study is mainly based on interview data and could therefore be extended by ethnographic investigations of CSR managers' work or by observations of CSR managers' language use in their everyday work. Originality/value: The study is part of a growing empirical literature that investigates the role of individual actors in developing and implementing CSR in organizations and, in particular, the role of CSR practitioners. It contributes to the development of the literature on CSR-driven change within business organizations.